Animal Models of Osteoarthritis Part 1–Preclinical Small Animal Models: Challenges and Opportunities for Drug Development - Rios, Jaqueline Lourdes; Sapède, Dora; Djouad, Farida; Rapp, Anna E.; Lang, Annemarie; Larkin, Jonathan; Ladel, Christoph; Mobasheri, Ali (John Wiley & Sons Inc., 2022)
Osteoarthritis (OA) is the most common form of arthritis and a major source of pain and disability in the adult population. There is a significant unmet medical need for the development of effective pharmacological therapies for the treatment of OA. In addition to spontaneously occurring animal models of OA, many experimental animal models have been developed to provide insights into mechanisms of pathogenesis and progression. Many of these animal models are also being used in the drug development pipeline. Here, we provide an overview of commonly used and emerging preclinical small animal models of OA and highlight the strengths and limitations of small animal models in the context of translational drug development. There is limited information in the published literature regarding the technical reliability of these small animal models and their ability to accurately predict clinical drug development outcomes. The cost and complexity of the available models however is an important consideration for pharmaceutical companies, biotechnology startups, and contract research organizations wishing to incorporate preclinical models in target validation, discovery, and development pipelines. Further considerations relevant to industry include timelines, methods of induction, the key issue of reproducibility, and appropriate outcome measures needed to objectively assess outcomes of experimental therapeutics. Preclinical small animal models are indispensable tools that will shine some light on the pathogenesis of OA and its molecular endotypes in the context of drug development. This paper will focus on small animal models used in preclinical OA research. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC.
Keywords: drug development; guinea pig; mouse; osteoarthritis; preclinical animal model; rabbit; rat; zebrafish; Osteoarthritis/drug therapy; Reproducibility of Results; Animals; Drug Development; Arthritis, Experimental/drug therapy; Disease Models, Animal; Medical Laboratory Technology; General Biochemistry,Genetics and Molecular Biology; General Immunology and Microbiology; Health Informatics; General Neuroscience; Pharmacology, Toxicology and Pharmaceutics(all); Journal Article